2000
DOI: 10.1111/j.1471-0528.2000.tb13301.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised double‐blind placebo‐controlled trial of transcervical intrauterine local anaesthesia in outpatient hysteroscopy

Abstract: Objective To assess whether transcervical intrauterine instillation of local anaesthetic agent reduces Design F'rospective, randomised, double blind, placebo-controlled trial.Setting Outpatient hysteroscopy clinic in a university teaching hospital.Population Ninety women undergoing outpatient diagnostic hysteroscopy with or without endometrial biopsy.Methods Transcervical intrauterine instillation of 5 mL of 2% lignocaine into the uterine cavity before performing the procedure.Main outcome measures Evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 12 publications
1
32
0
1
Order By: Relevance
“…Although these studies are different from ours in terms of material and method, they are significant as they showed that intrauterine anesthesia decreased pain in many gynecologic procedures. A limited number of studies on intrauterine topical anesthesia is available in literature and in most of these studies, the effectiveness of intrauterine anesthesia was investigated either in hysteroscopy or in hysteroscopy combined with endometrial biopsy (5,(8)(9)(10)17). Endometrial biopsy taken during hysteroscopy is more invasive and potentially more disturbing than only endometrial biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these studies are different from ours in terms of material and method, they are significant as they showed that intrauterine anesthesia decreased pain in many gynecologic procedures. A limited number of studies on intrauterine topical anesthesia is available in literature and in most of these studies, the effectiveness of intrauterine anesthesia was investigated either in hysteroscopy or in hysteroscopy combined with endometrial biopsy (5,(8)(9)(10)17). Endometrial biopsy taken during hysteroscopy is more invasive and potentially more disturbing than only endometrial biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated the use of local anesthetics (i.e., lidocaine, mepivacaine) to lessen the pain experienced during minor gynecological procedures such as endometrial biopsy and office hysteroscopy. Most, but not all, of these studies reported reduced pain during the procedure (8)(9)(10). The main objective of the present study was to compare the effectiveness of paracervical block, intrauterine lidocaine and oral etodolac in decreasing pain caused by endometrial sampling.…”
Section: Sonuçmentioning
confidence: 99%
“…Two relatively small randomized double-blind studies using mepivacaine injected through the cervix prior to hysteroscopy or endometrial sampling found a beneficial effect [7,8]. Using lidocaine 2% prior to endometrial biopsy, Hui et al [9] also reported lower pain scores in the treated group, whereas both Lau et al [10] (90 patients) and Wong et al [6] (500 women) did not find any improvement in the pain experienced during hysteroscopy or endometrial sampling after lidocaine instillation (all three studies [6,9,10] were randomized and double-blind). The only randomized study using intrauterine lidocaine 2% gel [11] prior to Vabra endometrial sampling in 308 patients did not show any pain reduction in the lidocaine group.…”
Section: Discussionmentioning
confidence: 99%
“…No difference was found in pain scores between the lignocaine group and the placebo group. 9 However, the instillation of the study fluids was through an angiocatheter inserted only up to the internal os of cervix and it was not mentioned whether any attempt was made to keep the study fluid inside the uterine cavity to allow the local anaesthetic to act. Furthermore, hysteroscopy was performed before endometrial sampling.…”
Section: Discussionmentioning
confidence: 99%